Association between domestic pig farm's characteristics in relation to the African swine fever occurrence in Peninsular Malaysia - Pravina Vathi, R.; Siti Zubaidah, R.; Norhariani, M. N. (Department of Veterinary Services Malaysia, 2023)
As ASF outbreaks among domestic pig farms in Peninsular Malaysia involve farms of various scale with different numbers of pig populations, determination of the risk factors related to farm characteristics would be useful to develop and strategise risk-based preventive measures. The present study was conducted to determine the pig farms characteristics and related risk factors associated with the ASF outbreaks in domestic pig farms in Peninsular Malaysia. The association between the 441 domestic pig farm characteristics and the farms ASF status at the farm level was analysed using univariate and multivariate logistic regression. The farm characteristics included in the study are the season at the farm during the outbreak period, location of the farm based on the population of pigs, housing system, farm scale based on SPP, farm density, breed type, BOD, buffer zone and MyGap certification status. Meanwhile, ASF-positive farms are farms which had reported ASF cases confirmed through Real Time PCR (RT-PCR) method. Farms located in states with high pig populations and the season at the farm during the outbreak period were identified to be more likely exposed to ASF outbreaks. The finding of this study provides an important insight that farms located in states with high pig populations and the season during the outbreak period are significantly associated with the introduction of the ASFV into domestic pig farms.